Neural Correlates of Feedback Processing in Visuo-Tactile Crossmodal Paired-Associate Learning - Gui, Peng; Li, Jun; Ku, Yixuan; Li, Lei; Li, Xiaojin; Zhou, Xianzhen; Bodner, Mark; Lenz, Fred A.; Dong, Xiao-Wei; Wang, Liping; Zhou, Yong-Di (Frontiers in Human Neuroscience, 2018)
Previous studies have examined the neural correlates for crossmodal paired-associate (PA) memory and the temporal dynamics of its formation. However, the neural dynamics for feedback processing of crossmodal PA learning remain unclear. To examine this process, we recorded event-related scalp electrical potentials for PA learning of unimodal visual-visual pairs and crossmodal visual-tactile pairs when participants performed unimodal and crossmodal tasks. We examined event-related potentials (ERPs) after the onset of feedback in the tasks for three effects: feedback type (positive feedback vs. negative feedback), learning (as the learning progressed) and the task modality (crossmodal vs. unimodal). The results were as follows: 1) Feedback type: the amplitude of P300 decreased with incorrect trials and the P400/N400 complex was only present in incorrect trials; 2) Learning: progressive positive voltage shifts in frontal recording sites and negative voltage shifts in central and posterior recording sites were identified as learning proceeded; 3) Task modality: compared with the unimodal PA learning task, positive voltage shifts in frontal sites and negative voltage shifts in posterior sites were found in the crossmodal PA learning task. Taken together, these results provide insights into cortical excitability related to feedback processing of crossmodal PA learning.